2019
DOI: 10.18699/vj19.557
|View full text |Cite
|
Sign up to set email alerts
|

Identification of univalent chromosomes in monosomic lines of cotton (Gossypium hirsutum L.) by means of cytogenetic markers

Abstract: The lack of clear morphological markers of cotton chromosomes contributed to the development of an unconventional method for marking chromosomes using translocations. Today, tester translocation cotton lines represent the most complete set of cytological markers. The results of cytogenetic analysis of F1 hybrids obtained from crosses of monosomic cotton lines with translocation lines with identified chromosomes are presented. Cytogenetic identification and numbering of univalent chromosomes in 25 monosomic lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Line Mo17 was found to be monosomic for chromosome 22 of the D t subgenome based on the polymorphic BNL673 marker used here. Another previously identified marker, JESPR235, was also located on chromosome 20 or 22 of the D t subgenome [34]. These results suggested that line Mo17 is monosomic for chromosome 22 of the D t subgenome [36] (Table 1).…”
Section: Molecular Marker Analysis Of Unknown Monosomicsmentioning
confidence: 59%
See 1 more Smart Citation
“…Line Mo17 was found to be monosomic for chromosome 22 of the D t subgenome based on the polymorphic BNL673 marker used here. Another previously identified marker, JESPR235, was also located on chromosome 20 or 22 of the D t subgenome [34]. These results suggested that line Mo17 is monosomic for chromosome 22 of the D t subgenome [36] (Table 1).…”
Section: Molecular Marker Analysis Of Unknown Monosomicsmentioning
confidence: 59%
“…The identification of most monosomic lines was confirmed using SSR markers at the Center for Genomics and Bioinformatics of the Academy of Sciences of the Republic of Uzbekistan [30,31]. As a result, four monosomic lines from the Cytogenetic Collection of Uzbekistan (Mo11, Mo16, Mo19, and Mo93) were found to have chromosome 2 of the A t subgenome; 16 monosomic lines (Mo7, Mo31, Mo38, Mo58, Mo59, Mo60, Mo69, Mo70, Mo71, Mo72, Mo73, Mo75, Mo76, Mo79, Mo81, and Mo89) had chromosome 4 of the A t subgenome; five monosomic lines (Mo13, Mo34, Mo67, Mo92, and Mo95) had chromosome 6 of the A t subgenome; Mo27 had chromosome 7 of the A t subgenome; Mo48 line had chromosome 18 of the D t subgenome; and monotelodisomic line Mo21 lacks an arm of chromosome 11 of the A t subgenome [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In the first generations of hybrids created as a result of ecological-geographical cross-breeding of stem samples and varieties, it was observed that the formation of fiber yield caused wide variability under the influence of the genotype of US samples with high fiber yield, and the appearance of forms with positive transgressive characteristics [9]. According to the results of the observations [10], it was determined that the variability of most economic characteristics in cotton is expressed by a certain regularity [11][12][13]. As a result of the scientific research [5], it was found that the technological quality indicators of TM-11 ridge fiber obtained during the study of morphological and valuable economic characteristics of varieties, ridges, interspecies, hybrids were noted, and the number of cleistogamous flowers in hybrid combinations was high.…”
Section: Introductionmentioning
confidence: 99%